Concentrations of monoanhydrous sugars (firemarkers) in Hala Hu sediment core H11 - Bernhard Aichner; Alice Callegaro; Marcel T J van der Meer; Bernd Wünnemann; Dada Yan; Yongzhan Zhang; Carlo Barbante; Dirk Sachse (PANGAEA, 2021)
Concentrations of monoanhydrous sugars (firemarkers) were analysed in core H11 from Hala Hu, China. The lake is located on the northern margin of the Tibetan Plateau (97.24 - 97.47°E, 38.12 - 38.25°N, 4,078 m above sea level), along the modern marginal zone between the Asian Summer Monsoon (ASM) and westerlies influences. The core was drilled at the deepest point (65 m) of the lake and extends from 0 to 212 cm sediment depth. According to the age-model (Yan et al., 2020) the covered time period is modern - 9216 cal yr BP. Compounds were quantified by means of ion chromatography (IC Dionex ICS 5000, Thermo Scientific, Waltham, USA), coupled with a single quadrupole mass spectrometer (MSQ Plus™, Thermo Scientific), which was equipped with a CarboPac MA1™ column (Thermo Scientific, 2 mm x 250 mm) and an Amino Trap column (2 mm x 50 mm).
In: Aichner, B et al. (2021): Concentrations and δD values of biomarkers in sediment cores H7 and H11 from Hala Hu, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.933814